2001
DOI: 10.1016/s0896-6273(01)00415-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Attenuation of Electrical Activity in Drosophila Using a Genetically Modified K+ Channel

Abstract: We describe here a general technique for the graded inhibition of cellular excitability in vivo. Inhibition is accomplished by expressing a genetically modified Shaker K(+) channel (termed the EKO channel) in targeted cells. Unlike native K(+) channels, the EKO channel strongly shunts depolarizing current: activating at potentials near E(K) and not inactivating. Selective targeting of the channel to neurons, muscles, and photoreceptors in Drosophila using the Gal4-UAS system results in physiological and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
143
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(152 citation statements)
references
References 45 publications
9
143
0
Order By: Relevance
“…The w,rpr; ϩ;ϩ, w and Canton-S lines were from the Bloomington Stock Center (Indiana University, Bloomington, IN). The 1ϫ, 2ϫ, and 3ϫ electrical knock-out (EKO) lines have been described previously (White et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The w,rpr; ϩ;ϩ, w and Canton-S lines were from the Bloomington Stock Center (Indiana University, Bloomington, IN). The 1ϫ, 2ϫ, and 3ϫ electrical knock-out (EKO) lines have been described previously (White et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have demonstrated the efficacy of targeted suppression of neuronal excitability in analyzing neuronal function (White et al, 2001;Nitabach et al, 2002). Applying this approach, we suppressed membrane excitability in N CCAP to ask whether hormone secretion requires electrical activity in these neurons.…”
Section: Suppression Of Excitability In N Ccap Inhibits Wing Expansiomentioning
confidence: 99%
“…Molecular Biology. SDN was generated from the EKO construct (32). The UAS-EKO ϩ vector was cleaved at the end of the ORF and 3Ј to the coding region for the S1 transmembrane helix.…”
Section: Methodsmentioning
confidence: 99%
“…Larval K ϩ currents were examined by using a two electrode voltage clamp similar to above. Larvae were dissected in 0 mM Ca 2ϩ physiological saline with 0.5 mM EGTA to eliminate the I CF and I CS calcium currents (32). The muscle was clamped at Ϫ80 mV and stepped to ϩ30 mV in 10-mV increments.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was demonstrated that neuronal circuits can be manipulated by expressing mutated ion channels or G protein-coupled receptors (GPCRs). For example, the regional expression of a genetically modified K ϩ channel in Drosophila was able to reduce the excitability of targeted cells (i.e., muscle, neurons, photoreceptors) (1). Silencing of cortical neurons was achieved by binding of the peptide allostatin to its exogenously expressed receptor (2).…”
mentioning
confidence: 99%